Enterprise Content Management - Ćwiklicki, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the article Enterprise Content Management concept was discussed. Terminology issues were considered with ECM functions definition. The relations between ECM and some chosen modern IT concepts were presented. At the end ECM was evaluated based on the ground of literature findings. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 115-122